Impact Analysis of Energy Policy: Fuel Oil Subsidies and Global Warming Costs - Masria Hernawaty Simanjuntak; Djoni Hartono (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2024)
Global warming has become an increasingly urgent issue to address, with the use of fossil fuels being the major contributor to CO2 in the atmosphere. This has encouraged governments in various countries to focus on reducing greenhouse gas emissions. The fuel oil subsidy policy will affect fuel consumption patterns, which in turn will affect the cost of global warming. This study aims to analyze the impact of energy policies related to fuel subsidies on global warming costs in lower- and upper-middle-income countries. This study uses panel data for both categories of countries from 2015 to 2022. The analysis employed fuel oil subsidy and global warming cost data, along with relevant economic factors. The estimation method uses a Fixed Effect model with Driscoll-Kraay standard errors to address cross-sectional dependency in the panel data analyzed. The analysis results show that fuel oil subsidies have a significant influence on increasing the cost of global warming in lower- and upper-middle- income countries. Therefore, it is necessary to consider reducing fuel subsidies and strengthening carbon emission regulations to address the increasing impact of global warming.